O11 AURORA phase 3 study demonstrates voclosporin statistical superiority over standard of care in lupus nephritis (LN). (23rd March 2020) - Teng, YK Onno; Parikh, Samir V; Saxena, Amit; Solomons, Neil; Huizinga, Robert B
Abstract : Background: Voclosporin (VCS) is a novel high potency calcineurin inhibitor (CNI) with a favorable metabolic profile and a consistent predictable dose response potentially eliminating the need for therapeutic drug monitoring. The recently completed Phase 3 AURORA study builds on the favorable efficacy seen in the Phase 2 AURA-LV study in patients with active LN. The AURORA study was conducted in active LN patients to evaluate the efficacy and safety of VCS vs placebo in combination with mycophenolate mofetil (MMF, 2 g/day) and rapidly tapered oral steroids. Methods: AURORA is a global, randomized double-blind, placebo-controlled Phase 3 study with active LN. Key inclusion criteria include biopsy proven LN (Class III, IV, V) and proteinuria of > 1.5 mg/mg or > 2 mg/mg for Class V patients. The primary endpoint was renal response (RR) at 52 weeks defined as UPCR of ≤ 0.5 mg/mg, eGFR ≥ 60 mL/min or no confirmed decrease from baseline in eGFR of >20%, presence of sustained, low-dose steroids and no administration of rescue medication. Results: AURORA enrolled 357 adult LN patients. The RR rate was 40.8% for voclosporin versus 22.5% for control (OR: 2.65; 95% CI: 1.64, 4.27; p<0.001). Also, a significantly higher proportion of LN patients achieved pre-specified hierarchical secondary endpoints for voclosporin including: RR at 24 weeks, partial renal response (PRR) at 24 and 52 weeks, time to achieve UPCR ≤ 0.5 mg/mg, and time to 50% reduction in UPCR (table 1 ). The efficacy benefit of VCS on RR was seen across prespecified biopsy subgroups: for pure Class V LN (OR: 2.74; 95% CI: 0.78, 9.68), and for Class III/IV alone or in combination with Class V patients (OR: 2.63; 95% CI: 1.57, 4.41). Furthermore, all pre-specified subgroup analyses (age, sex, race, region, and prior MMF use) also favored VCS. The overall incidence of SAEs was similar in both groups (VCS 20.8% and control 21.3%), with infections most commonly reported (VCS 10.1% and control 11.2%). Overall mortality in the trial was low, with six deaths observed; one in the voclosporin arm and five in the control group. Additionally, at Week 52 the VCS arm showed no significant decrease in eGFR or increase in BP, lipids or glucose. Conclusion: The addition of VCS to MMF and low-dose steroids demonstrated superior efficacy to standard of care in active LN patients. The 104-week double-blind AURORA continuation study will provide longer term safety and efficacy data.